The reliability of the submaximal version of the Yo-Yo intermittent recovery test in elite youth soccer - Owen, C.; Jones, P.; Comfort, P. (Journal of Trainology, 2017)
Objectives: To determine the test-retest reliability of the submaximal version of the Yo-Yo Intermittent Recovery Test - Level 1 (Yo-Yo IR1-sub), which is a valid aerobic assessment. Design: Test-re-test. Methods: Elite youth soccer players (n = 10, age: 18.8 ± 0.5 years, height: 181.1 ± 4.9 cm, body mass: 74.2 ± 7.6 Kg) completed the Yo-Yo IR1-sub on two consecutive weeks to determine the reliability of a non-exhaustive alternative to maximal aerobic testing. Relative and absolute reliability of the Yo-Yo IR1-sub was assessed for heart rate response and recovery metrics (HR6, HR30, HR60, HR90, HR120, HRR30, HRR60, HRR90 and HRR120). Results: The Yo-Yo IR1-sub was determined to be a reliable alternative to maximal testing, with the final heart rate at the end of the 6 minute test (HR6) shown to be the most reliable metric (ICC = 0.96; SDD = 5.4 bpm). The percentage of heart rate recovered after 2 min (HRR120) was the most reliable recovery metric (ICC = 0.93; SDD = 4.6%). Conclusion: If maximal testing is not a feasible option, particularly during the competitive season or during the rehabilitation of an injured player, then a submaximal test is a reliable alternative to monitor fitness in elite young soccer players, with HR6 and HRR120 being the most stable parameters.